Unstable Proximal Femur Fractures Treated With Proximal Femoral Locking Plates: A Retrospective, Multicenter Study of 111 Cases. Issue 9 (September 2016) - Collinge, Cory A.; Hymes, Robert; Archdeacon, Michael; Streubel, Phillip; Obremskey, William; Weber, Timothy; Watson, J. Tracy; Lowenberg, David
Abstract : Objectives: A few small case series have found that proximal femur fractures treated with a proximal femur locking plate (PFLP) have experienced more failures than expected. The purpose of this study was to review the clinical results of patients with acute, unstable proximal femur fractures treated with proximal femoral locking plates in a large, multicenter patient cohort. Design: This is a retrospective clinical study. Setting: The study included patients from 12 regional trauma centers and tertiary referral hospitals. Patients: One hundred eleven consecutive patients with unstable proximal femur fractures stabilized with a PFLP and having required clinical and radiographic follow-up at a minimum of 12 months after injury. Intervention: Surgical repair of an unstable proximal femur fracture with a PFLP. Main outcome measurements: Treatment failures (failure of fixation, nonunion, and malunion) and need for revision surgery. Results: Forty-six patients (41.4%) experienced a major treatment failure, including failed fixation with or without nonunion (39), surgical malalignment or malunion (18), deep infection (8), or a combination of these. Thirty-eight (34%) patients underwent secondary surgeries, including 30 for failed fixation, nonunion, or both. Treatment failure was found to occur at a significantly higher rate in patients with major comorbidities, in femurs repaired in varus malalignment, and using specific plate designs. Conclusions: Proximal femoral locking plates are associated with a high complication rate, frequently requiring revision or secondary surgeries in the treatment of unstable proximal femur fractures. Given the high complication rate with PFLPs, careful attention to reduction, use of a PFLP implant, and consideration should be given to alternative implants or fixation techniques when appropriate. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.